Activity measurement of mixed complex radionuclide like 152Eu with different methods. (July 2022) - Ravindra, Anuradha; Kulkarni, D.B.; Sharma, Ritu; Dahiwale, S.S.; Dhole, Sanjay D.; Prasad S, Sajin; Sathian, V.
Abstract: 152 Eu has been standardized by three independent 4π β-γ coincidence counting systems with beta detectors as proportional counter, plastic scintillator and liquid scintillator along with the CIEMAT/NIST method. The average activity concentration by primary methods was linked to key comparison reference value (KCRV) by comparing it with that of 4π γ ionization chamber (GIC) whose calibration factor was determined from the KCRV (BIPM.RI(II)–K1.Eu-152 and CCRI(II)–K2.Eu-152) and deviates from GIC by ± 0.16% indicating good agreement within standard uncertainties. Highlights: Standardization of 152 Eu for establishing a link to the CCRI(II)–K2.Eu-152 intercomparison. 4π β-γ coincidence technique in the variant of efficiency extrapolation. Standardization by CIEMAT/NIST method. Activity measurements by 4π γ ionization chamber. Comparison of activity concertation by direct methods and ionization chamber.